Molecular weight, solubility and viscosity of β-Glucan preparations from barley pearling byproducts - Lee, Young-Tack; Puligundla, Pradeep; Schwarz, Paul B. (Penerbit Universiti Kebangsaan Malaysia, 2017)
β-Glucan, the representative dietary fibre component of barley, has received much attention, primarily due to its nutritional significance. In this study, β-glucans prepared from barley pearling byproducts were characterized with respect to their molecular weight, solubility and viscosity. Following the initial alkaline extraction, the crude β-glucan extract (45% purity) was further purified to approximately 90%. The isolated β-glucans exhibited a wide molecular weight range with peak molecular weight of less than 1 × 106 daltons. Solubilities of crude and purified β-glucans in water were lower than that of β-glucan in the native barley pearling byproducts. However, the aqueous solubility of purified β-glucan from pearlings was substantially higher than that of commercial β-glucan. Compared to the latter, purified β-glucan exhibited low apparent viscosity in aqueous solutions.